2012
DOI: 10.3109/13697137.2012.664831
|View full text |Cite
|
Sign up to set email alerts
|

Daidzein improves insulin resistance in ovariectomized rats

Abstract: We conclude that daidzein can improve insulin resistance induced by ovariectomy by decreasing weight gain, visceral fat accumulation, blood lipids, TNF-α, leptin and IL-6 levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
12
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 34 publications
4
12
1
Order By: Relevance
“…This could alter lipid transport, plasma lipoprotein composition, and concentrations [5] and therefore reduce CVD risk in PMW. In contrast to findings in ovariectomized rats, in which daidzein therapy over 12 weeks decreased weight gain and VAT [3], we did not observe effects of the IF intervention on body weight, body fat, and VAT in PMW, which is in line with the results of an animal study perfomed with an identical IF extract over 12 weeks in ovariectomized rats [33]. We are not aware of other studies in humans that investigated effects of an IF extract intervention on these parameters, except of a study for 3 months in PMW with soy protein and IF, in which also no significant effects on VAT have been shown [4].…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…This could alter lipid transport, plasma lipoprotein composition, and concentrations [5] and therefore reduce CVD risk in PMW. In contrast to findings in ovariectomized rats, in which daidzein therapy over 12 weeks decreased weight gain and VAT [3], we did not observe effects of the IF intervention on body weight, body fat, and VAT in PMW, which is in line with the results of an animal study perfomed with an identical IF extract over 12 weeks in ovariectomized rats [33]. We are not aware of other studies in humans that investigated effects of an IF extract intervention on these parameters, except of a study for 3 months in PMW with soy protein and IF, in which also no significant effects on VAT have been shown [4].…”
Section: Discussioncontrasting
confidence: 93%
“…We investigated IF effects on body fat, VAT, and body weight, because soy and IFs are discussed to be antiadipogenic and to impact body composition and body fat depots [3,4,33,52]. This could alter lipid transport, plasma lipoprotein composition, and concentrations [5] and therefore reduce CVD risk in PMW.…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, Cheong et al further showed that treatment with daidzein also caused a reduction in nonfasting blood glucose and urinary glucose excretion in KK‐AY/Ta jcl mice, a potent animal model of T2Ds . In ovariectomized rats, daidzein intake at a dose of 50 mg/kg/day decreased the gain in body weight, visceral fat, and the levels of serum insulin, glucose, lipid, insulin resistance, and the secretion of cytokines, namely TNF‐α, leptin, and adiponectin . Another study with high fat diet fed C57BL/6J mice reported the synergistic effect of daidzein and glycitin (0.06% mixture in diet, in the ratio of 3:1) in controlling diabetes and obesity‐related complications.…”
Section: Effect Of Daidzein On T2d Pathophysiologymentioning
confidence: 93%
“…Some studies showed that daidzein could promote adipogenic differentiation and fat deposition (Cho et al, 2010;Hirota et al, 2010;Li et al, 2011). On the other hand, some researchers reported that daidzein inhibited adipogenic differentiation and fat deposition (Cao, Zhang, Zou, & Xia, 2013;Kim et al, 2010;Rachoń, Vortherms, Seidlová-Wuttke, & Wuttke, 2007). On the other hand, some researchers reported that daidzein inhibited adipogenic differentiation and fat deposition (Cao, Zhang, Zou, & Xia, 2013;Kim et al, 2010;Rachoń, Vortherms, Seidlová-Wuttke, & Wuttke, 2007).…”
mentioning
confidence: 99%
“…The underlying molecular mechanism was the activation of peroxisome proliferator-activated receptor (PPARr; Cho, Kim, Burgess, & Kim, 2006;Dang & Löwik, 2010;Sakamoto, Naka, Ohara, Kondo, & Iida, 2014), which modulated the expression of several key molecules involved in insulin signalling, lipid metabolism and endocrine function in adipocytes (Cho et al, 2006;Dang & Löwik, 2010;Sakamoto et al, 2014). On the other hand, some researchers reported that daidzein inhibited adipogenic differentiation and fat deposition (Cao, Zhang, Zou, & Xia, 2013;Kim et al, 2010;Rachoń, Vortherms, Seidlová-Wuttke, & Wuttke, 2007). They illuminated that daidzein had oestrogenic properties and could bind to oestrogen receptor α and β (ERα and ERβ, respectively; Dang, Audinot, Papapoulos, Boutin, & Löwik, 2003;Dang & Löwik, 2010), which were the ligand-activated transcription factors for inhibiting adipogenic differentiation (Cooke, Heine, Taylor, & Lubahn, 2001).…”
mentioning
confidence: 99%